A new species of the water mite genus Kawamuracarus Uchida from Oman (Acari: Hydrachnidia) - Smit, Harry (Zootaxa, 2003)
A new hyporheic water mite, Kawamuracarus stocki n. sp. (Limnesiidae), is described from Oman. It is the first record of a water mite from this country.